Koreografi Tari Piriang Bakencak Di Sanggar Tari Tuah Sakato Kecamatan Pauah Kota Padang - Rafi Rafi; Herlinda Mansyur (SENDRATASIK UNP, 2019)
This article aims to reveal and describe the choreography of Piriang Bakencak dance at Sanggar Tuah Sakato in Kecamatan Pauh Kota Padang. This type of research is qualitative research using descriptive methods. This research instrument is self-research and assisted by supporting instruments such as stationery and cameras. Data types use primary data and secondary data. Data collection techniques are conducted by way of library studies, observations, interviews and documentation. The steps for analyzing data are data collection, data reduction, data presentation and withdrawal of conclusions. The results showed that Piriang Bakencak dance was a group-shaped creation that used the composition of the group, and was directed by a lift in the Koto Anau tradition. This Bakencak dish dance is a development of tradition with a choreography approach. In Piriang Bakencak dance There are elements of dance composition consisting of theme, motion, top design, floor design, dramatic design, music design, process, equipment and choreography group. It was concluded that Piriang Bakencak dance was directed by planning choreography by the fact. Because Piriang Bakencak dance in the start of an idea that is present from the tradition, and was directed in a form of a clear, then directed again with more new movements.